Role of Twitter as a Digital Platform in Sharing and Preserving Information on Indigenous Knowledge Systems: A content Analysis - Suri, Sameeksha; Vatsala, Pratyush; Singh, Raghuraj Pratap; Singh, Devendra; Gautam, Alok Sagar (Asian Journal of Interdisciplinary Research, 2026)
The study focuses on assessing the available information on IKS through digital platform like Twitter where people share, connect and has the accessibility to reach to the wider population. The objective focuses on developing a structure available on information dissemination, preservation and awareness related to Indigenous knowledge system (IKS). Through Qualitative content analysis (QCA) , the article assessed the frequencies of posts and usage of hashtag for awareness of the posts published on IKS during the years 2023-2025 by various verified government, private authorities and with the individual users for knowledge diffusion. The analysis reveals that digital curation of policies and preparedness of IKS is reflected in the engagements done through the twitter posts to cater the information on Indigenous knowledge system and its worldwide outreach. This study concluded that digital curation through Twitter platform plays a prominent role on the level of participation and in increasing the awareness outreach mechanisms by the Indian education system and individual users to digitize the movement of IKS and making the materials accessible online for public awareness. In conclusion, the findings supports the significance of social media platform Twitter in preserving the traditional knowledge by adaptation of the contemporary digital contexts.